Viruses and Nuclear Egress - Coen, Donald M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Viruses focuses on the topic of viruses and nuclear egress. Nuclear egress is a fascinating process by which herpesvirus nucleocapsids make their way from the nuclear interior to the cytoplasm. As nuclear egress and the viral proteins that orchestrate it differ from host processes and proteins in important ways, there is interest in targeting antiviral therapies to disrupt this process. Indeed, the recently approved drug maribavir acts in large part by inhibiting a step of nuclear egress. The Special Issue includes five reviews-three on nuclear egress of two alphaherpesviruses, herpes simplex virus and pseudorabies virus; one on a betaherpevirus, human cytomegalovirus; and one on a gammaherpesvirus, Epstein-Barr virus-and five research papers-two on alphaherpesviruses and three on human cytomegalovirus.